Enhancing Early Childhood Education through a Local Wisdom-Based K4 Pillar Module with an Ethnoscience Approach - Iqbal, Muhammad; Widya; Muttakin; Fuadi, Noval; Safitri, Maya (Universitas Pendidikan Ganesha, 2024)
The learning environment in early childhood education institutions still faces challenges in implementing the values of cleanliness, neatness, health, and security (K4 Pillars). This study aims to develop a K4 Pillar module based on local wisdom through an ethnoscience approach within the context of early childhood education. The research employs the Educational Design Research (EDR) method to produce an innovative educational product. The subjects of the study include randomly selected early childhood students and teachers. Data collection methods encompass questionnaires, observations, and interviews. Data analysis utilizes statistical techniques for quantitative data and thematic analysis for qualitative data. The research findings indicate that the majority of students (87.5%) strongly support the use of the module as a learning tool, emphasizing its critical role in early childhood education. However, most teachers (62.5%) did not attempt to link the module with local wisdom, and 75% did not employ an ethnoscience approach, highlighting the need for increased teacher engagement in integrating local cultural elements and ethnoscience concepts into teaching. High levels of support from both students and teachers (87.5%) for the local wisdom-based module with an ethnoscience approach underscore its potential to enhance the effectiveness of early childhood education. The study concludes that the local wisdom-based module with an ethnoscience approach has significant potential to improve the effectiveness of early childhood education.